Trust-Based Working Time and Organizational Performance: Evidence from German Establishment-Level Panel Data - Michael Beckmann; Istvàn Hegedüs (University of Basel, Center of Business and Economics (WWZ), 2011)
This paper empirically examines the impact of trust-based working time on firm performance using panel data from German establishments. Trust-based working time is a human resource management practice that involves a high degree of worker autonomy in terms of scheduling individual working time. From the theoretical viewpoint, trust-based working time may affect worker motivation positively as well as negatively. Therefore, at the establishment level the performance effects of trust-based working time remain an open question. The analysis shows that both establishment productivity and profitability increase with the diffusion of trust-based working time. Referring only to establishments with trust-based working time arrangements, both performance effects are estimated at about 1-2 percent, while in the full sample both per- formance effects are stronger ranging between about 2.5 and 5 percent.
Keywords: J24; J81; M50; 330; Trust-based working time; working time flexibility; firm performance; Arbeitszeitgestaltung; Vertrauen; Arbeitsproduktivität; Unternehmenswachstum; Deutschland